Experimental and numerical investigation on micro-motion characteristics of lightweight spacecraft - Dongjian Su; Yingjie Yang; Xiaomei Guo; Liqiu Shi; Taoyuan Zhang; Wei Zhang; Jiageng Zheng; Chunlei Jiang (PLoS ONE, 2026)
Accurate prediction of micro-motion characteristics is essential to the success of space mission operations. In this paper, the lightweight spacecraft is selected as the research object. Firstly, the micro-motion characteristic test device is designed to carry out the micro-motion experiment, and the micro-motion characteristic of the test device is numerically simulated to verify the accuracy of the model compared with test data. On this basis, the angular velocity interferences of different values and different directions are simulated, and it is verified that the transversal initial interference is much larger than the spinning angular velocity interference. The cloud images of transversal angular velocity and precession angle under different transversal initial interferences are calculated. The conclusions have some guiding significance for the influence of initial disturbance on the micro-motion characteristics of lightweight spacecraft.